Service quality and customers’ patronage decision of healthcare insurance products: in-depth interview approach - Rahman, Muhammad Sabbir; AbdelFattah, Fadi AbdelMuniem; Mohamad, Osman (Human Resource Management Academic Research Society, 2014)
The purpose of this qualitative research is to explore the role of service quality on customers’ patronage decision of Malaysian health insurance products. Through a critical review of the literature about service quality and customers’ patronage intention this research proposed a relationship of service quality, customer’s satisfaction, perceived value and corporate image on customer’s patronage intention. This research applied qualitative approach (in-depth interview) from 20 participants. This research is also the starting point for better understanding, in a dynamic way to discover the role of service quality on customers’ patronage decision of Malaysian healthcare insurance products. The outcome of this study allows researchers and policy makers to specify the antecedents of the service quality, customer satisfaction, perceived value and corporate image towards the clients’ patronage purpose in health insurance products in Malaysia, which has not previously explored yet.